A culture-sensitive palliative pastoral care with a focus on the African context - Alfred R. Brunsdon (In die Skriflig, 2019)
This article engages the issue of a culture-sensitive palliative pastoral approach with the African context in mind. It contemplates palliative pastoral care from a dual-wisdom approach and denotes palliative pastoral care as an expression of Christian faith care towards patients and their relational networks, aimed at spiritual growth which enables meaning-making in the context of illness and possible loss. It also investigates the notions of illness, healing and dying in an African context and highlights the spiritual, systemic and communal nature of these concepts within African thinking. The implication for a culture-sensitive palliative pastoral approach is sought in the meaningful accommodation of these beliefs within the framework of Christian faith care. The coordinates of pastoral hospitality, an embodied pastoral care of presence, accommodation of the collective, the practice of respectful Christian discernment and inhabitation theology are suggested as some of the coordinates that could facilitate a culture-sensitive palliative pastoral approach.